Preliminary Results on the Long-Term Effects of Dextromethorphan on MDMA-Mediated Serotonergic Deficiency and Volumetric Changes in Primates Based on 4-[18F]-ADAM PET/MRI - Yeh, Skye Hsin-Hsien; Kuo, Yu-Yeh; Huang, Wen-Sheng; Chiu, Chuang-Hsin; Yu, Tsung-Hsun; II, Leo Garcia Flores; Tsai, Chi-Jung; Cheng, Cheng-Yi; Ma, Kuo-Hsing (Frontiers in Neuroscience, 2022)
Alterations to the serotonergic system due to MDMA (ecstasy) consumption have been extensively documented. However, knowledge of the reversibility of these neurotoxic effects based on in vivo evaluations of serotonin transport (SERT) availability remains limited. This study aimed to evaluate the long-term neurotoxicity of MDMA after 66 months abstinence and explored whether Dextromethorphan, a noncompetitive N-methyl-D-aspartate (NMDA) receptor, could attenuate MDMA-induced neurotoxicity using 4-[18F]-ADAM, an imaging ligand that selectively targets SERT, with positron emission tomography technology (PET). Nine monkeys (Macaca cyclopis) were used in this study: control, MDMA, and DM+MDMA. Static 4-[18F]-ADAM PET was performed at 60 and 66 months after drug treatment. Serotonin transport (SERT) availability was presented as the specific uptake ratios (SURs) of 4-[18F]-ADAM in brain regions. Voxel-based region-specific SERT availability was calculated to generate 3D PET/MR images. Structural MRI volumetric analysis was also conducted at 60 months. Significantly decreased 4-[18F]-ADAM SURs were observed in the striatum and thalamus of the MDMA group at 60 and 66 months compared to controls; the midbrain and frontal cortex SURs were similar at 60 and 66 months in the MDMA and control groups. All eleven brain regions showed significantly lower (~13%) self-recovery rates over time; the occipital cortex and cingulate recovered to baseline by 66 months. DM attenuated MDMA-induced SERT deficiency on average, by ~8% and ~1% at 60 and 66 months, respectively; whereas significant differences were observed between the thalamus and amygdala of the MDMA and DM + MDMA groups at 66 months. Compared to controls, the MDMA group exhibited significantly increased (~6.6%) gray matter volumes in the frontal cortex, occipital cortex, caudate nucleus, hippocampus, midbrain and amygdala. Moreover, the gray matter volumes of the occipital cortex, hippocampus and amygdala correlated negatively with the 4-[18F]-ADAM SURs of the same regions. DM (n = 2) did not appear to affect MDMA-induced volumetric changes. The 4-[18F]-ADAM SURs, lower self-recovery rate and increased volumetric values indicate the occipital cortex, hippocampus and amygdala still exhibit MDMA-induced neurotoxicity after 66 months’ abstinence. Moreover, DM may prevent MDMA-induced serotonergic deficiency, as indicated by increased 4-[18F]-ADAM SURs and SERT availability, but not volumetric changes.